A Disturbance-Observer-Based Prescribed Performance Control Approach for Low-Earth-Orbit Satellite Trajectory Tracking - Zhou, Yitong; Chang, Jing; Chen, Weisheng (Remote sensing (Basel, Switzerland), 2025)
As the complexity of Low-Earth-Orbit (LEO) satellite tasks and their performance requirements increase, higher demands are placed on satellites’ ability to track mission trajectories, including their accuracy, speed, and capacity to resist external disturbances during operation. This paper proposes an anti-disturbance prescribed performance control scheme for LEO satellites. The scheme establishes a unified framework to accommodate the high-performance requirements of satellite observation, while also incorporating a disturbance observer within this framework to counteract unknown external disturbances. Unlike existing trajectory tracking control methods, the proposed control scheme allows for the flexible selection of performance functions to adapt to diverse satellite performance demands. By focusing on the distance between tracking errors and the performance function, this approach avoids the performance boundary issues faced by traditional prescribed performance control, thus preventing excessive energy consumption by the LEO satellite. Additionally, within the proposed control framework, a disturbance observer is implemented to provide real-time compensation for unknown disturbances while ensuring minimal control input usage for disturbance rejection. Our experimental results show that the proposed control scheme achieves consistent performance for the LEO satellite and successfully accomplishes mission trajectory tracking, even in the presence of unknown disturbances.